RESPON SISWA TERHADAP MODEL THINK TALK WRITE BERBANTUAN MEDIA IKLAN DALAM PEMBELAJARAN MENULIS TEKS PERSUASI DI SMP - Rosita Rosita (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This research is motivated by the difficulties experienced by students in writing persuasion text essay in midlle School . The facts in the field state that students are difficult to get ideas, develop ideas and apply language rules that should be in the text of persuasion. Therefore the researcher tries to apply the Think Talk Write (TTW) learning model with the help of advertising medias to overcome the problem. The formulation of the problem in this study is how are students' responses to learning to write persuasion text using the think talk write model assisted by advertising media ?. The method used in this research is descriptive qualitative and the instruments used are questionnaires. Based on data processing in this study there were 89.5% of responses that stated positive. Thus, learning to write persuasive texts with the model of think talk write assisted by advertising media in class VIII F, SMP received very good responses.